PENGARUH KOMPETENSI GURU TERHADAP PRESTASI BELAJAR SISWA DI SMPN 13 PEKANBARU - Putri, Lusi Yolanda; ', Sumarno; Syabrus, Hardisem (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstack: teacher competence is the mastery of knowledge, skills, values and attitudes held by teachers in their profession. Learning achievement is the resulting ability of students in the learning process. This study aims to determine the effect of teacher competence on learning achievement students. The population in this study were students of class VII and VIII of SMPN 13 Pekanbaru. The sampling technique in this study using a nonprobability sampling, sample in this study is 89 samples. Data were collected using questionnaires and documentation. Data were analyzed using simple linear regression analysis, F test with significance level of 0.05%. Based on the research showed that the experience of teacher competence simultaneously positive and significant impact on learning achievement. It is based on the analysis results, which show the calculation results F test > F table (20,587>3,95). The predictive ability of the variable teacher competence on the learning achievement in the study amounted to 19.1% (R Square .191) while the remaining 80.9% is influenced by other factors which are not included in this study.Keywords: teacher competence, student achievement